Developing countries in the GATT legal system - Hudec, Robert E. (Gower AldershotGB, 1987)
Examines GATT's legal relationship with developing countries. Describes the history of that relationship from the pre-war years to the mid 1980's. Examines the benefits developing countries can expect to derive from the current legal policy and compares the benefits offered by the alternative legal policy of fuller participation. Concludes that GATT's current legal policy has failed to serve interests of developing-country members and proposes several policy initiatives to begin reversal of that policy.